Bis-Halogen-Anthraniloyl-Substituted Nucleoside 5′-Triphosphates as Potent and Selective Inhibitors of Bordetella pertussis Adenylyl Cyclase Toxin - Geduhn, Jens (The American Society for Pharmacology and Experimental Therapeutics, 2011)
Whooping cough is caused by Bordetella pertussis and still constitutes one of the top five causes of death in young children, particularly in developing countries. The calmodulin-activated adenylyl cyclase (AC) toxin CyaA substantially contributes to disease development. Thus, potent and selective CyaA inhibitors would be valuable drugs for the treatment of whooping cough. However, it has been difficult to obtain potent CyaA inhibitors with selectivity relative to mammalian ACs. Selectivity is important for reducing potential toxic effects. In a previous study we serendipitously found that bis-methylanthraniloyl (bis-MANT)-IMP is a more potent CyaA inhibitor than MANT-IMP (Mol Pharmacol 72:526–535, 2007). These data prompted us to study the effects of a series of 32 bulky mono- and bis-anthraniloyl (ANT)-substituted nucleotides on CyaA and mammalian ACs. The novel nucleotides differentially inhibited CyaA and ACs 1, 2, and 5. Bis-ANT nucleotides inhibited CyaA competitively. Most strikingly, bis-Cl-ANT-ATP inhibited CyaA with a potency ≥100-fold higher than ACs 1, 2, and 5. In contrast to MANT-ATP, bis-MANT-ATP exhibited low intrinsic fluorescence, thereby substantially enhancing the signal-to noise ratio for the analysis of nucleotide binding to CyaA. The high sensitivity of the fluorescence assay revealed that bis-MANT-ATP binds to CyaA already in the absence of calmodulin. Molecular modeling showed that the catalytic site of CyaA is sufficiently spacious to accommodate both MANT substituents. Collectively, we have identified the first potent CyaA inhibitor with high selectivity relative to mammalian ACs. The fluorescence properties of bis-ANT nucleotides facilitate development of a high-throughput screening assay.